The Use Is Informational – Communication Process Engineering’s In Professional Training Of The Experts On Economic Cybernetics - Smilyanets, О.Г. (Journal of Information Technologies in Education (ITE), 2009)
In a paper the problem professionally preparations of the experts on economic cybernetics by tools is considered is informational – communication process engineering’s. The necessity of the experts on economic cybernetics for modern economy and role informational – communication in their professional activity is underlined. The disciplines in professional trainings of the experts on economic cybernetics and theme on these disciplines are analyzed which immediately are connected to informational – communication process engineering’s. The problems are considered which are connected to practical preparation of the experts of a specialist «Economic cybernetics».